Exchange rate volatility and growth in Morocco: An ARDL bound approach - Hinde HAFFOU; Hamid FAYOU; Nabil BOUBRAHIMI; Abdelmoumen BERJAOUI (African Scientific Journal, 2022)
The objective of this article is to study the impact of Exchange rate volatility on Moroccan economic growth, based on an ARDL model, on time series from 1990 to 2018 and an according an interpretativist epistemological approach.. The main results show that in the short term and in the long term, Exchange rate have a negative effect on economic growth. In the short term, the investment variable has an instant negative impact on growth in short term but non-significant in the long term. For openness, it has a positive impact on growth. However, in the short and long term, External Debt has not a significant impact on economic growth